Exploring the dynamics of cow milk quality: A bibliometric and scoping review of dairy cattle research - Mulianda, Randi; Anggrahini, Santika; Sofyan, Ahmad; Baihaqi, Zein Ahmad; Qomariyah, Novia; Harahap, Muhammad Ainsyar; Firison, Jhon; Winart, Erna; Julendra, Hardi; Hardian, Hendra; et al. (Journal of Advanced Veterinary and Animal Research, 2025)
This study examines the contributions of various countries to milk quality research over the past 27 years (1997–2024) using bibliometric analysis of data retrieved from the Scopus database. The study aims to highlight the efforts required by governments to enhance research in this field. The analysis employs bibliometric tools, including VOSviewer, Scimago Graphica, Bibliometrix, and Microsoft Excel, to visualize data and conduct network analysis. The findings indicate a 13% increase in the number of publications related to milk quality. China leads in the number of publications, with 1,178 documents, whereas Italy excels in journal publications, contributing 188 journals and 388 institutions, accounting for 27.80% of the global total. China also dominates research funding, with 159 institutions representing 26.63% of global funding entities. In terms of citation impact, the United States ranks first with 2,953 citations, followed by Italy, China, and Brazil. This study provides valuable insights into dairy cattle research, particularly milk quality, through bibliometric analysis and a scoping review. The findings can assist stakeholders in identifying research trends, gaps, and innovations, thereby informing strategies to enhance milk production, nutritional quality, and sustainable dairy practices. J. Adv. Vet. Anim. Res., 12(3): 956–974, September 2025 http://doi.org/10.5455/javar.2025.l956